An analysis of foreign statutes dealing with environmental liability with a view to the drawing up and promulgating of an environmental liability statute in South Africa to deal with the legal problems of civil liability for environmental damage - de Bruin, Sean (Department of Public Law, 2024)
This essay concerns civil liability for environmental damage and has as its focus, the drawing up of an Environmental Liability statute for South Africa. The approach taken in the essay is largely a comparative one, with topics being approached first from a general perspective and then with reference to various foreign statutes and the approach taken therein to the issues being discussed. The essay begins by analysing the problems with relying on the common law, as it is in South Africa, as a basis for civil liability. This will focus largely on the necessary common law requirements of Fault and Causation, and the particular problems encountered when applied to the area of environmental harm or damage claims. This section will also contain a brief explanation of why it is believed that a statutory form of liability should be introduced as opposed to, for example, allowing the situation to be self-regulated by contractual warranties and/ or indemnities. The essay then considers what the objectives of such a statute should be. The focus here is on whether the goals of Remediation and Prevention-are both attainable within the framework of a single statute and, if so, to what degree. The next section seeks to analyse exactly what the basis of liability for environmental harm or damage should be and how it should be structured in order to overcome the specific problems created by common law liability requirements. The focus here will be on which variant of the regimes broadly referred to as strict liability should be adapted for a prospective South African statute. The essay will examine whether liability should be defined in terms of general principles or rather by reference to certain specific criteria and also what approaches can be discerned to the problem which Causation presents for the potential plaintiff in an environmental liability suit. In both cases the essay will examine the option(s) adapted in various jurisdictions and the success and/ or problems encountered. This section will also cover the possibility of an Information Right for prospective plaintiffs and the desirability and legality of instituting a reverse onus on the defendant in an environmental liability suit. The scope of such a statute forms the content of the following section. The discussion here revolves around how damage to the environmental should be defined. The essay will examine the importance of defining what constitutes damage and will examine a range of options as have been adopted in foreign statutes, analysing their respective strengths and weaknesses. The essay then moves on to discuss what Defences should be available to a defendant charged with liability under the statute. Again, a range of defences shall be examined and the appropriateness and implications of each discussed. The question of who should be able to recover damages as against the various types of harm covered by the statute forms the basis of the next section. This section will focus on the issue of whom, if anyone, should be able to recover for ecological damage, especially with regard to what can be termed, the "unowned environment". Various options will be discussed and their suitability evaluated. The penultimate section of the essay deals with which parties should be held liable under a prospective statute, for harm or damage as covered by such an act. The question of multiple wrongdoers and how to deal with such a situation will be discussed. A comparative study will again be employed, analysing varying approaches taken in foreign jurisdictions. This section will also cover the issue of Lender Liability. The question of how to ensure that defendant's held liable will be able to pay, will also be discussed. The final section of the essay will involve a discussion of certain aspects of Remedial Liability. These will be the Definition of remediation, various Approaches to Remediation, how to ensure compliance with remediation orders and finally, a suggested procedure for remediation. This section will be followed by general conclusions drawn from analyses performed in the body of the essay.